2019
DOI: 10.1111/aor.13444
|View full text |Cite
|
Sign up to set email alerts
|

Finite element study of functionally graded porous femoral stems incorporating body‐centered cubic structure

Abstract: The mismatch between stiffness of the femoral dense stem and host bone causes complications to patients, such as aseptic loosening and bone resorption. Three‐dimensional finite‐element models of homogeneous porous (HGP) and functionally graded porous (FGP) stems incorporating body‐centered cubic (BCC) structures are proposed in this article as an alternative to the dense stems. The relationship between the porosity and strut thickness of the BCC structure was developed to construct the finite‐element models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…This higher stiffnesses of cementless dense Ti-6Al-4V alloy stems cause several complications such as poor bone ingrowth, stress shielding, risk of bone fracture, and even revision of surgery. Finite element models are used successfully to investigate the biomechanical behavior of tissues and implants [5][6][7][8][9][10][11][12][13][14][15]. Many published works have used finite element models of implants made of composites and porous biomaterials to overcome the aforementioned complications [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This higher stiffnesses of cementless dense Ti-6Al-4V alloy stems cause several complications such as poor bone ingrowth, stress shielding, risk of bone fracture, and even revision of surgery. Finite element models are used successfully to investigate the biomechanical behavior of tissues and implants [5][6][7][8][9][10][11][12][13][14][15]. Many published works have used finite element models of implants made of composites and porous biomaterials to overcome the aforementioned complications [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that micro-motion between the femoral stem and bone interface is negatively correlated with the stiffness of the femoral stem (Alkhatib et al, 2019b). The main purpose of designing stems with a porous internal structure is to reduce stiffness to avoid stress shielding of the bone, but the reduced stiffness may also cause excessive interface micromotion.…”
Section: Promotion Of Bone Ingrowthmentioning
confidence: 99%
“…Sami E. Alkhatib et al of Qatar University, Doha, Qatar investigated by three‐dimensional finite‐element models the use of homogeneous porous (HGP) and functionally graded porous (FGP) stems incorporating body‐centered cubic (BCC) structures as an alternative to the dense stems. Three levels of porosities (20%, 50%, and 80%) were modeled in HGP and FGP stems.…”
Section: Orthopedic Supportmentioning
confidence: 99%